2021
DOI: 10.3390/pathogens11010042
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Ability of Klebsiella pneumoniae to Form Biofilm and the Potential of Various Compounds to Eradicate It from Urinary Catheters

Abstract: Urinary infections related to the presence of bacterial biofilm on catheters are responsible for loss of patients’ health and, due to their high frequency of occurrence, generate a significant economic burden for hospitals. Klebsiella pneumoniae is a pathogen frequently isolated from this type of infection. In this study, using a cohesive set of techniques performed under stationary and flow conditions, we assessed the ability of 120 K. pneumoniae strains to form biofilm on various surfaces, including catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Moderate adhesion can be interpreted as positive biofilm production according to the analysis proposed by Stepanovic et al [ 50 ]. The quantification of biofilm biomass is presented in the study of Oleksy-Wawrzyniak and co-authors [ 51 ], where they analyzed the adherence of 118 isolates of K. pneumoniae on polystyrene plates from the crystal violet assay, and 51% of isolates showed biofilms with moderate adherence. This study also demonstrated K. pneumoniae ATCC 700603 adherence with the obtained value of OD 1.00 unit ± 0.35, corroborating the results shown in Figure 4 b.…”
Section: Resultsmentioning
confidence: 99%
“…Moderate adhesion can be interpreted as positive biofilm production according to the analysis proposed by Stepanovic et al [ 50 ]. The quantification of biofilm biomass is presented in the study of Oleksy-Wawrzyniak and co-authors [ 51 ], where they analyzed the adherence of 118 isolates of K. pneumoniae on polystyrene plates from the crystal violet assay, and 51% of isolates showed biofilms with moderate adherence. This study also demonstrated K. pneumoniae ATCC 700603 adherence with the obtained value of OD 1.00 unit ± 0.35, corroborating the results shown in Figure 4 b.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the results obtained in the study set, more than 87% of Gram-negative isolates are biofilm producers, in agreement with the literature, being detected around 84% in CVC-related infections with E. coli, K. pneumoniae, P. aeruginosa, and Acinetobacter spp. Consequently, urge for new therapies are urgently needed to inhibit and eradicated biofilms in catheter-associated infections, as postulated by several authors ( Gunardi et al., 2021 ; Maharjan et al., 2018 ; Oleksy-Wawrzyniak et al., 2021 ). Finally, Candida isolates equally demonstrated to be strong biofilm-formers, through their production of extracellular polysaccharides and hyphae morphology shift, showing a biofilm prevalence near 100% and so becoming an important threat in hospital-acquired infections ( Bekkal brikci benhabib et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…by shaking at 150 rpm for 30 min. The absorption of the staining cell solution was measured at the wavelength of 591 nm to determine the bacterial adhesion on the sample surfaces [ 42 ]. Thus, the absorbance ratio of crystal violet stain and initial cell density was determined at the wavelengths of 591 and 570 nm (A591 nm/A570 nm).…”
Section: Methodsmentioning
confidence: 99%